1994
DOI: 10.1073/pnas.91.9.3877
|View full text |Cite
|
Sign up to set email alerts
|

NMR observation of substrate in the binding site of an active sugar-H+ symport protein in native membranes.

Abstract: NMR methods have been adopted to observe directly the characteristics of substrate binding to the galactose-H+ symport protein GaIP, in its native environment, the inner membranes of Escherichia coli. Sedimented innermembrane vesicles containing the GaiP protein, overexpressed to levels above 50% of total protein, were analyzed by 13C magic-angle spinning NMR, when in their normal "fluid" state and with incorporated D-[1-'3C]glucose. Using conditions of cross-polarization intended to discriminate bound substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Highly amplified expression levels were achieved for some transporters (GalP, NucP, LacS, FucP) allowing substrate binding studies by ssNMR of these proteins in their natural membranes (Patching et al 2004a;Spooner et al 1999Spooner et al , 1998Spooner et al , 1994a. Nevertheless, in most cases proteins have to be solubilised from membranes, purified and reconstituted into phospholipids.…”
Section: Solubilisation Purification Choice Of Detergentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Highly amplified expression levels were achieved for some transporters (GalP, NucP, LacS, FucP) allowing substrate binding studies by ssNMR of these proteins in their natural membranes (Patching et al 2004a;Spooner et al 1999Spooner et al , 1998Spooner et al , 1994a. Nevertheless, in most cases proteins have to be solubilised from membranes, purified and reconstituted into phospholipids.…”
Section: Solubilisation Purification Choice Of Detergentsmentioning
confidence: 99%
“…This approach has been attempted on doubly labelled glucose and forskolin. Unfortunately, it was found that in fluid membranes at 2°C no substrate detection was possible, but freezing samples at Spooner et al (1994a) −35°C allowed an efficient double-quantum filtering and hence substrate detection, most likely due to restrictions of molecular motion. At this temperature, both bound and non-bound substrates start to become immobilised which makes dynamic filtering difficult (Appleyard et al 2000).…”
Section: Sugar Transporter Galpmentioning
confidence: 99%
See 3 more Smart Citations